Artemisinin resistance and malaria elimination: Where are we now? - Hanboonkunupakarn, Borimas; Tarning, Joel; Pukrittayakamee, Sasithon; Chotivanich, Kesinee (Frontiers in Pharmacology, 2022)
The emergence of artemisinin resistance is a major obstacle to the global malaria eradication/elimination programs. Artemisinin is a very fast-acting antimalarial drug and is the most important drug in the treatment of severe and uncomplicated malaria. For the treatment of acute uncomplicated falciparum malaria, artemisinin derivatives are combined with long half-life partner drugs and widely used as artemisinin-based combination therapies (ACTs). Some ACTs have shown decreased efficacy in the Southeast Asian region. Fortunately, artemisinin has an excellent safety profile and resistant infections can still be treated successfully by modifying the ACT. This review describes the pharmacological properties of ACTs, mechanisms of artemisinin resistance and the potential changes needed in the treatment regimens to overcome resistance. The suggested ACT modifications are extension of the duration of the ACT course, alternating use of different ACT regimens, and addition of another antimalarial drug to the standard ACTs (Triple-ACT). Furthermore, a malaria vaccine (e.g. RTS,S vaccine) could be added to mass drug administration (MDA) campaigns to enhance the treatment efficacy and to prevent further artemisinin resistance development. This review concludes that artemisinin remains the most important antimalarial drug, despite the development of drug-resistant falciparum malaria.